Never (Viking, Thorndike Press, 2021)
"Every catastrophe begins with a little problem that doesn't get fixed." So says Pauline Green, president of the United States, in Ken Follett's nerve-racking drams of international tension. A shrinking oasis in the Sahara Desert; a stolen US Army drone; an uninhabited Japanese island; and one country's secret stash of deadly chemical poisons: all these play roles in a relentlessly escalating crisis. Struggling to prevent the outbreak of world war are a young woman intelligence officer; a spy working undercover with jihadists; a brilliant Chinese spymaster; and Pauline herself, beleaguered by a populist rival for the next presidential election. "Never" is an extraordinary novel, full of heroines and villains, false prophets and elite warriors, jaded politicians and opportunistic revolutionaries. It brims with cautionary wisdom for our times and delivers a visceral, heart-pounding read that transports readers to the brink of the unimaginable." -- jacket.

Erak's ransom ((John Anthony)Ranger's apprentice, 7,, 2007)
On a mission to pay the ransom of a new ally, apprentice Will and his friends find themselves in a desert wasteland awash with enemies.

Truly like lightning (Farrar, Straus and Giroux, 2021)
Follows the experiences of a former Hollywood stuntman-turned-Mormon polygamist who is blackmailed by an ambitious developer to enroll his children in public school.

The desert challenge (Bear grylls adventures, ,, 2017)
"Sophie loves camp--except for all the creepy-crawlies. Getting trapped in the tent with a daddy longlegs is terrifying, and spiders make her scream. It's so embarrassing. But then a mysterious compass transports her to a fiercely hot desert, where Bear Grylls, her guide, is watching. The sun is beating down, and together they must trek to find water and overcome the dangers lurking in the dunes ... Will Sophie find her survival spirit, face up to her fears and make her way back to her friends?"--Page [4] cover.